IMPLEMENTASI METODE LINEAR CONGRUENTIAL GENERATOR PADA GAME PUZZLE BERBASIS ANDROID - Aah Sumiah; Rendi Ridwanul Hakim (Universitas Kuningan, 2020)
Games has become one thing in everyday life. Formerly, the game is only used as a means of entertainment alone, but now the game has become the extent of its function. For example, game can be a mean of learning, business land, and competed as one of the sport by professionals. The development of platform games can also be seen directly by the community, the games only played on computers and consoles in past time, however now it has entered the era of mobile games. Puzzle game is a game that displays pieces of the image where the pieces of the image is scrambled arrangement to provide its own challenge to arrange it. This puzzle game is a game of drawing pieces with the rules of a piece can only be moved by sliding it into empty space. Generally people who play the puzzle, take a long time in completing the game. This is because in the puzzle there is no additional information available to help searching the solution when the process of arranging the pieces into a challenge for those who play it. Images of a puzzle will be scrambled using the Linear Congruential Generator (LCG) method. Linear Congruential Generator using an initial state then with a special formula will generate a pseudo-random number. The initial state used is taken from a variety of sources that are considered quite random. Thus, the Linear Congruential Generator will produce a series of numbers that resemble random numbers. Linear Congruential Generator is widely used today, it eases the implementation and speed as the main factor why Linear Congruential Generator is used.Keywords : Games, Puzzle Games, Linear Congruential Generator (LCG)